“Is It a Good Thing?”: Martha Stewart and Homemaking - Tye, Diane (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1997)
Martha Stewart Omnimedia is a tremendously successful enterprise disseminating homemaking advice through books, magazines, newspaper columns and television programmes. In the tradition of works like Janice Radway’s feminist analysis of women’s romance novels, a study that privileges audience voices, this article examines a popular culture form aimed at homemakers. Relying on interviews with five homemakers who watch Martha Stewart on television or read the Martha Stewart Living magazine, I explore Stewart’s influence on these individuals’ domestic skills acquisition and on their perceptions and practices of homemaking. Centrally, I consider homemakers’ interpretations of Martha Stewart’s depictions of domestic labour, depictions which they consider as escapism. I ask, as Janice Winship does in her discussion of a woman’s magazine and its interconnections to consumption and capitalism: “..why these fantasies, this escape...?” (1983: 45).